Pesan Dakwah Dalam Novel Bumi Cinta Karya Habiburrahman El Shiray - Nuhin; Bunyamin; Muhammad Abdi, Andi (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
Generally, da'wah is an activity of reciting the Koran or lectures carried out by ustaz or ustazah and religious leaders. As time goes by, various types of media have emerged to make it easier to convey da'wah messages. This can enrich existing da'wah strategies, one of which is through literary media in the form of novels. Based on this, the researcher tried to study a novel entitled Bumi Cinta by Habiburrahman El Shirazy. The aim is to find out how the da'wah message is contained in the novel Bumi Cinta, with three classifications of Islamic da'wah material contained in Surah Al-Fatihah, including the Da'wah Message of Akidah, Akhlak and Sharia. Then, from the da'wah messages, the recipients of the da'wah as told in the novel Bumi Cinta are aligned. This research uses a qualitative approach. Then the object or data obtained is in the form of a novel narrative text. Data collection techniques use library research and documentation. The data obtained was analyzed using Ferdinand De Saussure's semiotic theory. This theory has a sign system consisting of signifiers (signifier) and sign (signified), to explore the meaning contained in the narrative text or object being studied.